KEY REQUIREMENTS FOR BUILDING AN ENLIGHTENED SOCIETY IN THE PROCESS OF NATIONAL RENAISSANCE - Gulzoda Uzoqova (Scholar Express Journal, 2025)
The process of national renaissance encompasses a profound and multifaceted transformation aimed at revitalizing a nation’s historical legacy, cultural values, institutional frameworks, and socio-economic structures. It transcends mere political or economic reforms, demanding a holistic societal transformation grounded in knowledge, ethical principles, and civic engagement. Central to this transformation is the establishment of an enlightened society — one comprised of informed, morally responsible, critically thinking, and actively participating citizens
Keywords: historical legacy; cultural values; institutional frameworks